Uranium Effect on Osteocytic Cells In Vitro. (17th April 2019) - Hurault, Lucile; Creff, Gaelle; Hagège, Agnès; Santucci-Darmanin, Sabine; Pagnotta, Sophie; Farlay, Delphine; Den Auwer, Christophe; Pierrefite-Carle, Valérie; Carle, Georges F
Abstract: Once absorbed in the body, natural uranium [U(VI)], a radionucleotide naturally present in the environment, is targeted to the skeleton which is the long-term storage organ. We and others have reported the U(VI) negative effects on osteoblasts (OB) and osteoclasts (OC), the main two cell types involved in bone remodeling. In the present work, we addressed the U(VI) effect on osteocytes (OST), the longest living bone cell type and the more numerous (> 90%). These cells, which are embedded in bone matrix and thus are the more prone to U(VI) long-term exposure, are now considered as the chief orchestrators of the bone remodeling process. Our results show that the cytotoxicity index of OST is close to 730 µM, which is about twice the one reported for OB and OC. However, despite this resistance potential, we observed that chronic U(VI) exposure as low as 5 µM led to a drastic decrease of the OST mineralization function. Gene expression analysis showed that this impairment could potentially be linked to an altered differentiation process of these cells. We also observed that U(VI) was able to trigger autophagy, a highly conserved survival mechanism. Extended X-ray absorption fine structure analysis at the U LIII edge of OST cells exposed to U(VI) unambiguously shows the formation of an uranyl phosphate phase in which the uranyl local structure is similar to the one present in Autunite. Thus, our results demonstrate for the first time that OST mineralization function can be affected by U(VI) exposure as low as 5 µM, suggesting that prolonged exposure could alter the central role of these cells in the bone environment.